STRUGGLING INDONESIAN EFL UNIVERSITY STUDENTS GOING TO MALL: ANY SIGNIFICANT IMPACTS? - Parudani, Iyehezkiel; Effendi, Taufiq; Rahmi, Gita; Syafrudin, Syarifah Azharina (Universitas Gunadarma, 2021)
Mobile-assisted Language Learning (MALL) has been globally popular. Yet, experimental studies investigating the results of different treatments between additional MALL and standard MALL implementations in Indonesian university context are still understudied. This research sought to investigate the extent to which additional MALL activities as a treatment to an EFL experimental group of university students could improve their English given the limited class time and large sized classes. The subjects of this study were two second semester classes of English Literature students. The experimental class, a low-performing group, was asked to watch a youtube video twice or thrice a week in addition to the standard online learning during the Covid-19 pandemic while the controlled class, a better performing group, was not given this treatment. The findings revealed that (1) experimental students significantly improved their pronunciation, intonation, vocabulary and fluency but not their formal assessment results; (2) though assigned additional MALL activities, the experimental group, due to limited financial ability for internet, spent roughly as much time as the controlled group; ((3) bad internet connection and low economic affordability contributed significantly to the less satisfactory result of MALL; (4) due to the standard online learning during the pandemic, both experimental and controlled students experienced increased exposures, enthusiasm, motivation, range of independent activites, autonomy and English ability; (5) real time students’ collaboration is challenging. This study suggests that MALL somehow allows greater English improvement and autonomy development and therefore is recommended that universities and respective local governments especially in remote areas provide the necessary supports.